Towards pervasive mashups in embedded devices: comparing procedural and declarative approach. (1st January 2013) - Salminen, Arto; Mikkonen, Tommi
The web has become pervasive. This has led to a paradigm shift, where applications live on the web as services, where they can be accessed with different types of terminals. The ability to dynamically combine content from numerous sources, and the ability to instantly publish services worldwide has opened up entirely new possibilities for software development. Such applications that aggregate content from the web are commonly referred to as mashups. Unfortunately, for various reasons, the browser is inadequate for hosting complex mashups, in particular when considering embedded devices and subsystems that are not readily available in the web. In this paper, we introduce two environments, intended for hosting context-aware mashups on embedded devices. These environments have different approaches as one can be used to compose mashups in procedural and another in declarative fashion. As an example, we describe a location-aware mashup composed for both environments.